Penggunaan Dialek Nagoya pada Manga Yatogame Chan No Kansatsu Nikki - Reny Wiyatasari; Vyan Restu Utomo (KIRYOKU, 2022)
This study aims to determine the factors that underlie speakers using the Nagoya dialect, which is a dialect used in the city of Nagoya, the capital of Aichi prefecture. The research data is collected from the Japanese comics (manga) entitled YATOGAME CHAN NO KANSATSU NIKKI. The data collection method used is the referential method. The data were analyzed using the equivalent and descriptive qualitative method. Based on the results of the analysis known that the factors underlying the use of the Nagoya dialect are group membership factors, age, and situation.